Irrigating with arsenic contaminated groundwater in the Bengal Delta: a review of mitigation options. - Senanayke, N.; Mukherji, Aditi (International Water Management Institute, 2012)
This Highlight reviews 34 papers that deal with interventions aimed at reducing negative impacts of irrigating with Arsenic (As) rich water. These studies show that there are six broad groups of interventions: deficit irrigation, soil fertilization, growing crops other than paddy, switching to As tolerant paddy cultivars, cooking methods to reduce As content in cooked rice and nutritional supplements. All these treatments are effective in reducing the uptake of As in grains and its accumulation in soil and increasing crop yields compared to control group, but the extent of these impacts vary. From a policy perspective, it is encouraging that these interventions are able to mitigate the negative impact of As in irrigation water to varying extent. This is because poor farmers in the Bengal delta are likely to continue to use groundwater for irrigation in the foreseeable future in the absence of any other viable options.